Isolation and Characterization of “Terrein” an Antimicrobial and Antitumor Compound from Endophytic Fungus Aspergillus terreus (JAS-2) Associated from Achyranthus aspera Varanasi, India - Goutam, Jyoti; Sharma, Gunjan; Tiwari, Vinod K.; Mishra, Amrita; Kharwar, Ravindra N.; Ramaraj, Vijayakumar; Koch, Biplob (Frontiers in Microbiology, 2017)
The present study aimed at characterizing biological potentials of endophyte Aspergillus terreus JAS-2 isolated from Achyranthus aspera. Crude extracted from endophytic fungus JAS-2 was purified and chemically characterized by chromatographic and spectroscopic studies respectively. Spectral assignment of NMR (nuclear magnetic resonance) data, 1H proton and 13C carbon analysis along with FTIR data elucidated the structure of compound as 4,5-Dihydroxy-3-(1-propenyl)-2-cyclopenten-1-one. After purification and identification a set of experiment was conducted to explore efficacy of compound. Results revealed that on accessing the antifungal activity of compound, growth diameter of tested phytopathogenic fungi was reduced to 50% at higher concentration taken (10µgµl-1). Compound exhibited in-vitro bacterial cell inhibition at 20µgml-1 concentration along with moderate antioxidant behavior. Evaluation of anticancer activity against lung cancerous cell line (A-549) exhibited its IC50 value to be 121.9±4.821µgml-1. Further cell cycle phase distribution were analyzed on the basis of DNA content and evaluated by FACS (Fluorescence Activated Cell Sorting) and it was revealed that at 150µgml-1 of compound maximum cells were found in sub G1 phase which represents apoptotic dead cells. Terrein (4, 5-Dihydroxy-3-(1-propenyl)-2-cyclopenten-1-one) a multi-potential was isolated from endophytic fungus JAS-2, from well recognized medicinal herb Achyranthus aspera. To best of our knowledge, this is the first report of “Terrein” from endophytic derived fungus. This compound had also exhibited anticancer and antifungal activity against lung cell line A-549 and Bipolaris Soronkiniana which is causal organism of many plants disease. Hence endophytes are serving as alternative sources of drug molecules. Keyword: Antimicrobial, Environmental mycology, Anti-cancer activity, Terrein